Continuous Renal Replacement Therapy in Venovenous Extracorporeal Membrane Oxygenation: A Retrospective Study on Regional Citrate Anticoagulation. Issue 3 (March 2020) - Giani, Marco; Scaravilli, Vittorio; Stefanini, Flavia; Valsecchi, Gabriele; Rona, Roberto; Grasselli, Giacomo; Bellani, Giacomo; Pesenti, Antonio M.; Foti, Giuseppe
Abstract : Systemic infusion of unfractionated heparin (UFH) is the standard anticoagulation technique for continuous renal replacement therapy (CRRT) during extracorporeal membrane oxygenation (ECMO), but often fails to avoid CRRT circuit clotting. The aim of this study was to assess, in patients undergoing CRRT during venovenous ECMO (vv-ECMO), the efficacy and safety of adding regional citrate anticoagulation (RCA) for CRRT circuit anticoagulation (RCA + UFH group) compared with the sole systemic heparin anticoagulation (UFH group). We performed a retrospective chart review (2009–2018) of patients treated with CRRT during ECMO. We evaluated filter life span, rate of CRRT circuit clotting, and coagulation parameters. The incidence of citrate anticoagulation-related complications was recorded. Forty-eight consecutive adult patients underwent CRRT during vv-ECMO in the study period. The incidence of CRRT circuit clotting was lower in the RCA + UFH group (11% vs. 38% in the UFH group, p < 0.001). Log-rank survival analysis demonstrated longer circuit lifetime for RCA + UFH group. No complication ascribable to citrate anticoagulation was recorded. Regional citrate anticoagulation resulted a feasible, safe, and effective technique as additional anticoagulation for CRRT circuits during ECMO. Compared with systemic heparinization only, this technique allowed to reduce the rate of CRRT circuit clotting. Abstract : Supplemental Digital Content is available in the text.